ASSIGNMENT OF EMPLOYEES IN SMEs THROUGH SOFTWARE TO ENHANCE SUSTAINABLE COMPETITIVE ADVANTAGE (CASE STUDY ON DEDE MOTORCYCLE SEMARANG) - Nuryanto, Imam (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2013)
This study was conducted to determine the assignment of employees. SMEs should have a sustainable competitive advantage, an effort that can be achieved is the optimal assignment of employees. Dede Motorcycle is an SMEs engaged in services. For Dede Motorcycle, customer is everything, therefore the customer is very important and need to be maintained so as not to move to another company or competitor. Problems that occur when this method is not optimal assignment of employees ( mechanics ). Â  The sampling method was done by using purposive sampling. Method of data collection by interview to conduct a discussion with Dede Motorcycle Semarang on research instruments, determine the number of employees and number of jobs and value the skills competencies of each employee. Then compared before and after the assignment method using the software POM. Â  Analysis of the results obtained by the fact, that the Employee Assignment before using the software POM, the value of the assignment showed a value of 265 (optimal value before POM) and after using the software POM, Optimal Allocation Assignment, Sodiq working Modification, Nurohim working Electrical, Mustakim working Tune-Up and Yanto working Over-Hole with the optimal value of the acquisition amounted to 335 (optimal value assignment). With optimal assignment SMEs can improve competitive advantage (competitiveness) sustainable.